1990
DOI: 10.1093/jn/120.12.1624
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Metabolism in Mature and Immature Rats Fed Animal and Plant Protein

Abstract: In two feeding experiments immature (180 g) and mature rats (370 g) were fed a semi-purified diet containing 20% of a protein source (casein, wheat gluten, soybean or potato protein) for 4 wk. Food supply was restricted to 15 g daily. As compared to casein, plant proteins induced significantly lower concentrations of plasma total cholesterol and high density lipoprotein (HDL) cholesterol. The plasma cholesterol increase associated with aging was not prevented by consumption of casein, soybean or potato protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…Plant products have been reported to have a hypocholesteromic effect in human, terrestrial animal, and fish (Lees et al, 1977;De Schrijver, 1990;Kaushik et al, 1995). The present study clearly showed that dietary RPI inclusion gradually reduce serum cholesterol levels in L. rohita fingerlings.…”
Section: Discussionsupporting
confidence: 68%
“…Plant products have been reported to have a hypocholesteromic effect in human, terrestrial animal, and fish (Lees et al, 1977;De Schrijver, 1990;Kaushik et al, 1995). The present study clearly showed that dietary RPI inclusion gradually reduce serum cholesterol levels in L. rohita fingerlings.…”
Section: Discussionsupporting
confidence: 68%
“…The greater absorption was accompanied by higher blood levels of triglycerides in pigs fed on PPC than on CAS while the total cholesterol concentration did not differ. These findings are contradictory to the hypolipidaemic effect of potato protein observed in rats (De Schrijver, 1990) and its hypocholesterolaemic but not hypolipidaemic, effect found in pigs (Spielmann et al, 2009). Pigs and not rats, are considered as a better model of lipid metabolism when related to humans.…”
Section: Concentration Of Protein and Lipid Metabolites In Blood (Expmentioning
confidence: 63%
“…De Schrijver has reported that the plasma cholesterol concentration in rats fed with plant protein such as wheat gluten was significantly lower than that in those fed casein, and that this result was caused by the excretion of fecal neutral steroids and bile acid. 26) In this study, wheat gluten and dietary fiber in the bread might have been related to the lipid metabolism. 23,26) The liver cholesterol concentration in the BP group was significantly (P < 0:05) higher than that in the CN group; although the reason for this remains unclear, it may be speculated that the increase in liver cholesterol concentration was due to the lower acidic sterol excretion by the BP group than by the BBP group.…”
Section: Discussionmentioning
confidence: 77%